Effect of geometry on clasp retention force: a finite element analysis study - Ruizhen Chen; Yao Chen; Zhiqiang Zheng; Jie Lin (BMC Oral Health)
Abstract Purpose The retention force of a realistic clasp is influenced by multiple, interrelated factors, which complicates the identification of the fundamental relationship between clasp geometry and retention force. While realistic clasps exhibit various shapes, they share basic geometric elements such as length, diameter, and curvature. Simpler geometries are often more conducive to identifying the underlying issues. The aim is to investigate the relationship between clasp geometry and retention force using finite element analysis. Methods A three-dimensional clasp model was created in ANSYS 19.0 (ANSYS, USA). Two types of models were analyzed: rod-shaped clasps with varying lengths (1–15 mm) and diameters (0.6–1.6 mm), and bending clasps with different base widths (6–12 mm) and heights (0.5–5 mm), all made from cobalt-chromium alloys. For the rod models, stress and retention force were assessed by applying displacement loads and analyzing data with nonlinear regression. For the bending models, a similar analysis was conducted for varying base widths and heights. Results Maximum stress consistently concentrated at the clasp base. In rod models, retention force decreased with the third power of length and increased with the fourth power of diameter. For bent specimens, the retention force was approximately inversely proportional to the cube of the base width and inversely proportional to the first power of the height. Conclusions Finite element analysis revealed distinct functional relationships between clasp geometry and retention force. Further laboratory validation is required.